Fractional anisotropy in patients with disproportionately enlarged subarachnoid space hydrocephalus - Radovnický, Tomáš; Adámek, D; Derner, Milouš; Sameš, Martin (Acta neurochirurgica, 2016)
BACKGROUND: Disproportionately enlarged subarachnoid space hydrocephalus (DESH) findings on MRI were described as a prognostic factor for responsiveness to the treatment of idiopathic normal pressure hydrocephalus (iNPH). Our premise is that DESH could be associated with compression of the cerebral white matter. Microstructural changes can be identified using diffusion tensor imaging (DTI), specifically fractional anisotropy (FA). The aim of this study is to compare FA in iNPH patients with and without DESH and healthy controls. METHODS: We analysed 1.5-T MRI scans of patients fulfilling the criteria of probable or possible iNPH and positive supplementary tests before and after surgery (ventriculo-peritoneal shunt). FA was measured in the anterior and posterior limb of the internal capsule (PLIC) and in the corpus callosum. Patients were divided into the DESH and non-DESH group. These data were also compared to FA values in the control group. RESULTS: Twenty-seven patients and 24 healthy controls were enrolled. DESH was present in 15 patients and lacking in 12. Twenty-three iNPH patients were shunt responders (85.2 %), and 4 were non-responders (14.8 %). All patients in the DESH group were shunt responders. In the non-DESH group, eight patients were responders (66.7 %). A significant difference between the DESH and non-DESH group was found in the FA of the PLIC. The mean value of FA in the PLIC was 0.72 in the DESH group and 0.66 in the non-DESH group. After the surgery FA decreased in both groups. In the DESH iNPH group FA PLIC decreased to 0.65 and in the non-DESH iNPH group to 0.60. In the healthy controls, the mean FA in the PLIC was 0.58. CONCLUSION: DESH on MRI scans is related to a higher FA in the PLIC with a decrease after the surgery. It reflects a more severe compression of the white matter than in non-DESH patients or healthy volunteers. DESH patients had better outcome than non-DESH patients. This study confirmed the importance of DESH as a supportive sign for iNPH.
Keywords: senioři; Hydrocephalus, Normal Pressure; Anisotropy; ventrikuloperitoneální zkrat; Middle Aged; mužské pohlaví; Diffusion Tensor Imaging; anizotropie; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ženské pohlaví; Humans; zobrazování difuzních tenzorů; lidé středního věku; Ventriculoperitoneal Shunt; Female; Aged; normotenzní hydrocefalus; lidé; Male